Entrepreneurship skills for new ventures - Kimball, David Charles, 1959-; Lussier, Robert N. (New York : Routledge, Taylor & Francis Group, 2021)
"As business schools expand their entrepreneurship programs and organizations seek people with entrepreneurial skills, it has become clear that the skills and mindset of an entrepreneur are highly valued in all business contexts. This latest edition of Entrepreneurship Skills for New Ventures continues to focus on helping students develop entrepreneurial skills, whether they seek to become entrepreneurs or employees. Focusing on the entrepreneurial start-up process, the fourth edition of Entrepreneurship Skills for New Ventures takes the reader through the steps of selecting, planning, financing, and controlling the new venture. The authors cover multiple forms of new ventures, as well as ways to utilize entrepreneurial skills in other contexts, encouraging students to engage with the material and apply it to their lives in ways that make sense for them. Skill development features include: Entrepreneurial profiles of small business owners; Personal applications for students to apply questions to their new venture or a current business; Global and domestic cases; Elevator pitch assignments which put students in the venture capitalist position; Application exercises and situations covering specific text concepts; Business plan prompts to help students construct a business plan over the course of a semester Featuring pedagogical tools like review questions and learning outcomes, and online materials which expands upon skill development and offers instructor resources, the fourth edition of Entrepreneurship Skills for New Ventures is the perfect resource for instructors and students of entrepreneurship"--
OCLC-licensed vendor bibliographic record.
Keywords: Entrepreneurship; New business enterprises -- Management; Strategic planning; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / New Business Enterprises; BUSINESS & ECONOMICS / Small Business